Studies on Spectral Properties of Uranyl(VI) Complexes with o-Hydroxy Oximes - Mehta, B.H.; Ghogale, Preetam (Asian Journal of Chemistry, 2010)
Three oximes were synthesised by reacting 5-nitrosalicylaldehydl 2-hydroxy-1-naphthaldebyde and resacetophenone with hydroxylamine- hydrochloride. These oximes were used to synthesise uranyl(VI) complexes using aqueous uranyl acetate. Uranyl complexes were characterised by elemental analyses, molar conductivity, electronic absorption spectra and infrared spectra. On the basis of experimental data probable structures were assigned to these uranyl complexes.